Treadmill Exercise Alleviates Circadian Rhythm Disruption-Induced Memory Deficits by Activation of Glucocorticoid Receptor and Brain-Derived Neurotrophic Factor-Dependent Pathway - Kim, Sung-Eun (Int Neurourol J, 2019)
PURPOSE: Circadian rhythm affects learning process, memory consolidation, and long-term memory. In this study, the alleviating effect of exercise on circadian rhythm disruption-induced memory deficits was investigated. METHODS: BMAL1 knockdown transgenic mice (BMAL1 TG) were used as the BMAL1-TG group and the BMAL1-TG with treadmill exercise group. Female C57BL/6J mice of the same age were used as the wildtype group and the wildtype with treadmill exercise group. The mice in the treadmill exercise groups performed running on a motorized treadmill under the dark-dark conditions for 8 weeks. Short-term memory, nonspatial object memory, and spatial learning memory were determined using stepdown avoidance test, novel object-recognition test, and radial 8-arm maze test. Immunohistochemistry for doublecortin and 5-bromo-2’-deoxyuridine was conducted for the determination of hippocampal neurogenesis. Using the western blot analysis, we determined the expressions of glucocorticoid receptor (GR) and factors related to the neurogenesis and memory consolidation, such as brain-derived neurotrophic factor, tyrosine kinase B, p44/42 mitogen-activated protein kinase, cyclic AMP-responsive element binding protein, phosphatidylinositol 3-kinase, protein kinas B, protein kinase C alpha, early-growth-response gene 1. RESULTS: Circadian rhythm disruption impaired memory function through inhibiting the expressions of GR and the factors related to neurogenesis and memory consolidation. Treadmill exercise improved memory function via enhancing the expressions of GR and above-mentioned factors. CONCLUSIONS: Treadmill exercise acts as the zeitgeber that improves memory function under the circadian rhythm disrupted conditions.